2022
DOI: 10.3390/jof8050454
|View full text |Cite
|
Sign up to set email alerts
|

New Antibacterial Chloro-Containing Polyketides from the Alga-Derived Fungus Asteromyces cruciatus KMM 4696

Abstract: Six new polyketides acrucipentyns A–F (1–6) were isolated from the alga-derived fungus Asteromyces cruciatus KMM 4696. Their structures were established based on spectroscopic methods. The absolute configurations of some compounds were assigned by the modified Mosher’s method, ROESY data analysis, as well as biogenetic considerations. Acrucipentyns A–E were identified to be the very first examples of chlorine-containing asperpentyn-like compounds. The cytotoxic and antimicrobial activities of the isolated comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…83 Five new chlorinated polyketides, acrucipentynes A−E (189− 193), are found in the fungus Asteromyces cruciatus KMM 4696, which is associated with an unnamed alga from Vostok Bay in the Sea of Japan. 84 The epoxide acrucipentyne F corresponding to D and E is also present in this fungus. To varying degrees, the new acrucipentynes inhibit sortase A activity, bacterial growth, and biofilm formation, and decrease LDH release from human keratinocytes.…”
Section: ■ Marine Fungimentioning
confidence: 84%
See 1 more Smart Citation
“…83 Five new chlorinated polyketides, acrucipentynes A−E (189− 193), are found in the fungus Asteromyces cruciatus KMM 4696, which is associated with an unnamed alga from Vostok Bay in the Sea of Japan. 84 The epoxide acrucipentyne F corresponding to D and E is also present in this fungus. To varying degrees, the new acrucipentynes inhibit sortase A activity, bacterial growth, and biofilm formation, and decrease LDH release from human keratinocytes.…”
Section: ■ Marine Fungimentioning
confidence: 84%
“…Five new chlorinated polyketides, acrucipentynes A–E ( 189 – 193 ), are found in the fungus Asteromyces cruciatus KMM 4696, which is associated with an unnamed alga from Vostok Bay in the Sea of Japan . The epoxide acrucipentyne F corresponding to D and E is also present in this fungus.…”
Section: Marine Fungimentioning
confidence: 99%
“…It was previously shown that strain A. cruciatus KMM 4696 can produce the first chlorine-contained monocyclic cyclohexanols containing a 3-methylbutenynyl unit that obviously originated from a tetraketide precursor [ 7 ]. Benzopyranes 10 and 11 obviously originated from the same precursor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, chlorine-containing compounds acrucipentyns A–F were isolated by us from Asteromyces cruciatus KMM4696 fungus associated with brown alga Sargassum pallidum , and these compounds showed significant antibacterial activity against Staphylococcus aureus [ 7 ]. The detailed separation of the non-polar part of this fungal extract resulted in the isolation of a number of new and known anthraquinone derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…As the most active compound, 210 also showed moderate cytotoxicity (IC 50 = 14.8 μM) [ 97 ]. Some other new antibacterial chloro-containing polyketides were identified from alga-derived fungus [ 98 ]. Furthermore, isochromophilone IX ( 212 ) presented outstanding antibacterial activity against MRSA (MIC = 50 μg/mL) [ 99 ].…”
Section: Aromaticsmentioning
confidence: 99%